Some agent theory for the semantic web. - Fass, Leona F.
We take the position that for any goal achievable on the Semantic Web, there will be a "best" system of Web-dwelling software agents to realize that goal, and that such a system may be discovered effectively. The process of determining the "best" agent system may be overseen by a distinguished Manager Agent. But with realistic time and space constraints, and the dynamic nature of the Semantic Web, finding an approximating system may be acceptable. The approximation then may be adapted iteratively, to approach the ideal. We show that very practical researchers have looked at software agents and Semantic Web problems in a similar way, determining approximating sub-optimal systems and subsequently adapting them. Their applied research confirms that theory provides a good foundation for practice.
Keywords: Computing methodologies; Artificial intelligence; Knowledge Representation Formalisms and Methods; Semantic networks; Theory of computation; Analysis of algorithms and problem complexity; Nonnumerical algorithms and problems; Distributed artificial intelligence; Multiagent systems; Algorithms; Design; Theory; Multi-agent systems; Software agents; The semantic web; Theoretical foundations; Web services